Residents’ Attitudes and Social Innovation Management in the Example of a Municipal Property Manager - Kabus, Judyta; Dziadkiewicz, Michał (Energies (Basel), 2022)
Corporate responsibility is an effective management strategy which, through conducting social dialogue at the local level, contributes to increasing the competitiveness of enterprises at a global level and simultaneously shaping favourable conditions for social and economic development. A review of the literature on the subject provided the theoretical motivation to undertake an emirical study of the implemented social innovations by the property manager and their reception by resource residents. The main aim of this study was to diagnose the attitudes of residents towards the implementation of social innovations by the municipal property manager. The research presented in the above article has been conducted in the first and second quarter of 2021 among residents of the Department of Housing “TBS” (ZGM TBS) in Częstochowa, Silesian voivoideship, Poland. The research was conducted using the survey method. The measurement instrument was a prepared questionnaire. The survey was completed by 362 respondents (n = 362). To confirm the hypotheses, an analysis using the Mann–Whitney U test and the Anov Kruskal–Wallis test were performed. In order to demonstrate the statistical significance of the assumptions made, the conducted tests were also supported by the p-value test. The research results undertaken made it possible to identify social innovations implemented by the municipal manager, both those which are expected by residents and those which tenants consider superfluous.